Green Technology Innovation and Sustainable Performance: A Resource-Based Mediation Model of Circular Economy Adoption - Noviany, Henny; Safri (Indonesian Scientific Publication, 2025)
This study investigates how Green Technology Innovation (GTI) enhances Sustainable Business Performance (SBP) through the mediating role of Circular Economy (CE) practices, offering an integrative framework that addresses firm-level sustainability strategy. A quantitative, cross-sectional survey was conducted among 250 manufacturing firms. Using validated instruments, data were collected on GTI activities, CE implementation, and SBP outcomes. Structural Equation Modeling–Partial Least Squares (SEM-PLS) was employed to test direct and indirect relationships, with bootstrapping applied to assess mediation effects.Findings reveal that GTI positively influences both CE adoption (β = 0.64, p < 0.001) and SBP (β = 0.32, p < 0.01). CE also directly enhances SBP (β = 0.58, p < 0.001) and partially mediates the GTI–SBP relationship (indirect β = 0.37, p < 0.001). Sectoral and geographic variations in adoption were noted, with larger and high-tech firms demonstrating higher engagement. The results validate the Natural Resource–Based View (NRBV), indicating that firms with integrated GTI–CE strategies gain competitive and environmental advantages. CE was found to serve as both a performance enabler and a resilience mechanism. GTI and CE are complementary strategies for achieving SBP. Firms should embed CE into their innovation strategies to maximize outcomes. Policymakers are encouraged to promote supportive regulatory and fiscal environments. Future studies should explore longitudinal effects and sector-specific dynamics.